2018
DOI: 10.1155/2018/1027397
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Steep Trendelenburg Positioning on Retinal Structure and Function during Robotic-Assisted Laparoscopic Procedures

Abstract: Purpose Robotic-assisted laparoscopic radical prostatectomy (RALP) has become a standard treatment choice for localized prostate cancer. RALP requires a steep Trendelenburg position, which leads to a significant increase in intraocular pressure (IOP). This study evaluated the effect on the retinal structure and function in patients undergoing RALP. Methods Standard automated perimetry (SAP) and optical coherence tomography (OCT) were performed in 20 males scheduled for RALP at 1 month and 1 day before the oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…Therefore, these authors concluded that the retinal pathologic changes were unlikely to be due to transient visual field defects. We recently examined normal subjects and reported that pre- and postoperative observations revealed no significant changes in the retinal structure and function [8]. Mathew et al also evaluated normal subjects at 1 month postoperatively and reported that none of the patients developed visual field or RNFL changes [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, these authors concluded that the retinal pathologic changes were unlikely to be due to transient visual field defects. We recently examined normal subjects and reported that pre- and postoperative observations revealed no significant changes in the retinal structure and function [8]. Mathew et al also evaluated normal subjects at 1 month postoperatively and reported that none of the patients developed visual field or RNFL changes [12].…”
Section: Discussionmentioning
confidence: 99%
“…In order to be able to maintain both the eye structure and physiology, the IOP is an essential factor. Furthermore, previous studies have reported finding a correlation between intraoperative IOP changes and the clinical postoperative ophthalmological outcomes [68]. Taketani et al examined visual field defects at 1 week after surgery using optical coherence tomography (OCT) and reported finding that the visual field returned to normal within 3 months after the surgeries in all cases, even though there were no abnormal findings in the fundus, retinal nerve fiber layer (RNFL) thickness, or optic disc morphology [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies of steep Trendelenburg positioning and robotic-assisted prostatectomy hysterectomy have small sample sizes and are in patients without glaucoma. 179,[194][195][196][197] The biggest study included 51 nonglaucomatous subjects who underwent robotic-assisted laparoscopic prostatectomy or hysterectomy while positioned in steep Trendelenburg. No changes were found at 3 months in retinal nerve fiber layer or ganglion cell complex thickness, foveal threshold, mean deviation, or pattern standard deviation.…”
Section: Review Articlementioning
confidence: 99%
“…The propagation time of the ultrasonic signal measured by the signal receivers A and B is τ 1 , τ 2 . Assuming that the propagation speed of the ultrasonic signal in the air medium is c, the distance u and v between the positioning target and the signal receivers A and B can be calculated as [19].…”
Section: Figure 1 Schematic Diagram Of System Positioningmentioning
confidence: 99%